Recruitment of pial collaterals and carotid occlusive disease in large-vessel occlusion ischemic stroke - Helwig, Niklas; Wagner, Marlies; Seiler, Alexander (Frontiers in Neurology, 2024)
Background and purpose Despite the fundamental role of pial collateral vessels in limiting the progression of ischemic tissue injury in acute stroke with large vessel occlusion (LVO), in addition to the fact that collateral vessel abundance varies naturally from person to person for genetic reasons, there is limited knowledge regarding potential factors contributing to inherent interindividual variation in pial collateral supply. As it has been repeatedly hypothesized that chronic carotid occlusive disease may favor pial collateralization, we aimed to investigate the association between quantitatively assessed leptomeningeal collateral supply and pre-existing carotid stenosis in patients with acute stroke due to LVO. Materials and methods Patients with proximal middle cerebral artery (MCA) occlusion with or without additional internal carotid artery (ICA) occlusion were included. The degree of collateral supply was quantitatively assessed based on signal variance in T2*-weighted time series in perfusion-weighted magnetic resonance imaging (PWI). Patients were stratified into two groups according to quantitative collateral status (poor and fair to good collateral supply). The prevalence of high-grade ICA stenosis (≥70%) was evaluated in both groups. Results A total of 98 patients (mean age 68.8 ± 16.1 years, n = 52 (53.1%) of whom were female individuals) with MCA and/or ICA occlusion were included in the final analysis. Out of these patients, 42 had poor collateral supply, while 56 exhibited fair to good collateral supply. Additionally, 18 patients showed ipsilateral high-grade ICA stenosis. After classifying the entire cohort based on their collateral status (poor vs. fair to good collateral supply), there was no significant difference in the proportion of the patients with ipsilateral high-grade ICA stenosis between the two groups. Specifically, 6 (14.3%) patients had poor collateral supply, and 12 (21.1%) patients had fair to good collateral supply. The odds ratio (OR) was 1.58, with a 95% confidence interval (CI) of 0.490–5.685 and the p-value of 0.440. In the entire patient cohort, signal variance-based collateral supply was significantly correlated with initial stroke severity (r = −0.360, p < 0.001), baseline ischemic core volume (r = −0.362, p < 0.001), and functional outcomes (score on the modified Rankin Scale) at discharge (r = −0.367, p < 0.01). Conclusion In this study, we performed a quantitative and observer-independent MRI-based collateral assessment in patients with LVO. We found no significant difference in the prevalence of pre-existing high-grade ICA stenosis between patients with fair to good collateral supply and those with poor collateral supply. The potential influence of demographic and clinical variables on pial collateral supply in patients with acute stroke warrants further exploration in future studies. MRI-based collateral supply is significantly related to initial stroke severity, ischemic core volume, and early functional outcomes.